Morals and science education - Rolston, Holmes, 1932-2025, author; Springer Reference, publisher (Colorado State University. Libraries, 2015)
Facts and causes are the domain of science and values and duties the domain of ethics. Morality must be chosen, entered into, practice in life, in ways that science does not. The sciences open up new possibilities with which traditional moral systems are unfamiliar, such as genetic modification. They also reveal natural history and human cognitive uniqueness that can be challenging to interpret. Biologists join ethicists in respect for life. After 400 years of science, the value questions are as sharp and painful as ever.
Keywords: biodiversity; neuroscience; natural history; science; ethics; values; respect for life; evolution